LGBTQ+ Bullying and Cyberbullying: Beyond Sexual Orientation and Gender Identity - Ojeda, Mónica (Victims & offenders, 2024)
LGBTQ+ bullying has a serious impact on young people’s well-being. Many studies have analyzed this phenomenon in terms of the sexual orientation and/or gender identity of the victim, or taking just homophobic aggression into account. This view over-simplifies and limits our understanding of the phenomenon. The present study analyzes, exhaustively, in 2552 adolescents, the prevalence of both general and LGBTQ+ bullying and cyberbullying in accordance with age, assigned sex, gender identity, sexual orientation and gender expression. The results highlight the need to avoid general approaches and to consider the full spectrum of Affective-Sexual, Bodily, and Gender Diversity, given the differences that exist in the risk of victimization and cybervictimization among LGBTQ+ students. They also underscore the importance of taking these differences into consideration in order to design effective prevention and intervention strategies.